Expert System For Diagnosing Goat Diseases Using The Forward Chaining Method (case study of SHQ Nura Farm) - Saputra, Aditya Aji; Efendi, Tino Feri; Pakarti, Moch Bagoes (Institut Teknologi Bisnis AAS Indonesia, 2024)
Goats are livestock that provide many benefits for human life, such as meat and milk. Healthy goats will produce quality meat and milk. good so it increases the selling price. Disease can interfere with the growth of goats and if left untreated can kill goats. Most of the farmers still have low knowledge about disease control, whereas goat livestock diseases thrive in tropical climates such as Indonesia. The number of experts available in rural areas is still limited. Information technology such as expert systems can help farmers carry out early treatment of diseases that attack goat livestock. An expert system is a system that tries to adopt human knowledge to a computer, so that the computer can solve a problem as experts usually do. The research here uses the forward chaining method to solve problems that exist in goat livestock. Forward Chaining is a reasoning inference method that uses facts to reach conclusions. The results obtained are in the form of a simple website application to help determine goat diseases and are easy to operate by entering symptom facts of 2 - 3 visible symptoms. The results of the system testing showed 80% accuracy in diagnosing diseases in goats.